1994
DOI: 10.1577/1548-8659(1994)123<0779:mcoumr>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Comparisons of Upper Missouri River Sturgeons

Abstract: Morphometric comparisons were made among three isolated populations of pallid sturgeon Scaphirhynchus albus and shovelnose sturgeon S. platorynchus from the upper Missouri River. Six measurements were made on 89 pallid and 204 shovelnose sturgeons. Means of several morphometric characteristics were statistically different between populations of both species. Pallid sturgeon means showed proportional trends relative to location on the river. Toward the headwaters, relative head and interrostral lengths were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 3 publications
1
63
0
Order By: Relevance
“…Fish and Wildlife Service, 2006) have propelled the question of species discrimination to the forefront of pallid sturgeon recovery in the Middle (mouth of Missouri River to mouth of Ohio River) and Lower (mouth of Ohio River to Gulf of Mexico) Mississippi River (MMR and LMR, respectively). Recently suggested phenomena that have confounded Scaphirhynchus species discrimination include interspecific hybridization (Carlson and Pflieger, 1981; Phelps and Allendorf, 1983; Carlson et al., 1985; Keenlyne et al., 1994a,b; Simons et al., 2001; Snyder, 2002; Wills et al., 2002; Tranah et al., 2004), geographic patterns in genetic and morphometric variation (Campton et al., 2000; Tranah et al., 2001; Everett et al., 2003; this study) and regionally unique microsatellite alleles (Rob Wood, pers. comm.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Fish and Wildlife Service, 2006) have propelled the question of species discrimination to the forefront of pallid sturgeon recovery in the Middle (mouth of Missouri River to mouth of Ohio River) and Lower (mouth of Ohio River to Gulf of Mexico) Mississippi River (MMR and LMR, respectively). Recently suggested phenomena that have confounded Scaphirhynchus species discrimination include interspecific hybridization (Carlson and Pflieger, 1981; Phelps and Allendorf, 1983; Carlson et al., 1985; Keenlyne et al., 1994a,b; Simons et al., 2001; Snyder, 2002; Wills et al., 2002; Tranah et al., 2004), geographic patterns in genetic and morphometric variation (Campton et al., 2000; Tranah et al., 2001; Everett et al., 2003; this study) and regionally unique microsatellite alleles (Rob Wood, pers. comm.…”
Section: Introductionmentioning
confidence: 72%
“…has demonstrated that shovelnose and pallid sturgeon are often difficult to distinguish until a certain body size is attained (Bailey and Cross, 1954; Snyder, 2002; Kuhajda et al., 2007). In the case of the pallid sturgeon, therefore, geographic range may also be a possible influence on morphology, with changes reflected in relative distance from headwaters due to developmental responses to water temperature (Ruban and Sokolov, 1986; Keenlyne et al., 1994b; Campton et al., 2000) or due to underlying genetic differences (Campton et al., 2000; Tranah et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, morphometric analyses of sturgeon fish to assess the degree of phenotypic plasticity in this species have rarely been conducted (Hilton and Schaefer 2002). Instead, morphological differences between wild and hatchery-reared sturgeon (Ruban andSokolov 1986, Ruban 1989) have been described for stock identification (Guenette et al 1992, Keenlyne et al 1994) and subspecies identification (Vasil'eva 2009). On the other hand, for different species the level of phenotypic plasticity has been well documented (Cramon-Taubadel et al 2005, Wintzer and Motta 2005, Wessel et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The pallid sturgeon (Scaphirhynchus albus Forbes and Richardson, 1905) is indigenous to large rivers of the central United States, primarily the Missouri and Mississippi river drainages (Lee et al 1980;Carlson et al 1985;Keenlyne et al 1994). Until it was recognized as a separate species, it was often mistakenly identified as a shovelnose sturgeon (Scaphirhynchus platorhynchus) in commercial fishery reports (Carlson et al 1985).…”
Section: Introductionmentioning
confidence: 99%